Prevalence of factors associated with cardiovascular disease and their relationship with work absenteeism in a government office (2019)
Introduction: Cardiovascular disease is the first cause of death in the world. This phenomenon is attributed to life styles, such a sedentarism, ingestion of high calorie foods, and alcohol and tobacco consumption. This leads to an increase in the rates of obesity, dyslipidaemia, and hypertension. These then become risk factors that directly affect the prevalence of disease and death of cardiovascular origin, which consequently represents a significant health problem in the working population. Objective: To determine the factors associated with cardiovascular disease and their relationship with work absenteeism in a government office in the City of Bogota, Colombia. Materials and methods: A descriptive study was carried out using the work records of 214 employees. Sociodemographic, clinical-cardiovascular, and work variables were also recorded. An analysis was performed on the independent variables and the outcome, and a logistic regression model was prepared using work absenteeism as a dependent variable. Results: The prevalences of the sample were: smoking, 13.1%; alcohol consumption, 35.1%; sedentarism, 39.7%; overweight or obese workers, 54.2%; and elevated total cholesterol, 43.9%. Treatment was being received for hypertension in 29.9%, with 4.7% for diabetes, and 21.5% for lipid disorders. Conclusion: The prevalence of risk factors associated with cardiovascular disease is similar to that found in other studies on the working population. The regression model showed that the variables marital status, obesity, treatment for hypertension, diastolic blood pressure level, and length of service, behaved as predictive variables of work absenteeism. © 2019 Sociedad Colombiana de Cardiología y Cirugía Cardiovascular